THE ROLE OF CORPORATE GOVERNANCE AND ACCOUNTING INFORMATION QUALITY IN REDUCING FINANCIAL CORRUPTION - Assistant Lecturer: Alaa Abbood Kadhim; Assistant Lecturer: Mariam Dawod Noman (Scholar Express Journals, 2025)
The research aims to define the conceptual framework of corporate governance and accounting information quality and to demonstrate their role in reducing financial corruption. To achieve the goal, the researchers relied on designing a questionnaire for the purpose of acquiring the relevant data to test the research hypotheses. The questionnaire was constructed based on a five-point Likert scale to ensure consistency in measuring respondents’ individuals. 100 questionnaires were distributed, and 90 of them were answered. The research field represented the academic sector, specifically "Tikrit University" and "University of Samarra". Meanwhile, the research community represented academics (teaching staff and researchers) in all of these two universities, in addition to auditors. The key results of the research can be summarized are that the application of corporate governance provides financial disclosures of superior quality that enhance the realization of the institution’s goals and reducing financial corruption. Appropriate financial information helps in making decisions in the institution through feedback, which helps in reducing financial corruption. There is a strong consensus among the respondents from "Tikrit University" and "University of Samarra" regarding the presence of expressions related to the role of "Accounting Information Quality" in mitigating "Financial Corruption within the research field. This is evidenced by the calculated mean values for these statements, which exceeded the hypothetical mean value of (3), which confirms the availability of all phrases, in addition to the high percentage of relative importance. For all phrases, it is noted that the phrase "Reliable accounting information reassures stakeholders regarding the company's financial position" achieved the highest level of availability. The research recommended that companies be required to implement corporate governance due to its positive impact on all stakeholders, as well as to achieve reliable and credible financial oversight reports. It also recommended increasing disclosure of the institution's economic outputs to benefit stakeholders and facilitate the detection of financial corruption. It also emphasized the need to use reliable and transparent accounting standards to ensure the accuracy of financial reports.
Keywords: Corporate Governance; Accounting Information Quality; Financial Corruption